Acute Ecotoxicity and Bioconcentration Tests for Se(IV) in Nile tilapia (Oreochromis niloticus) - da Costa, Pedro Henrique [UNESP]; Ferreira, Nathalia dos Santos [UNESP]; Nogueira, Ana Rita de Araujo; Azevedo, Eduardo Bessa; Gonzalez, Mario Henrique [UNESP] (American Chemical Society (ACS), 2024)
Selenium is one of the most important trace element micronutrients for the global biota, mainly due to its role in protecting against oxidative stress. However, this element can become toxic when present at concentrations slightly higher than those needed for metabolic purposes. It can be transferred through the food chain toward higher trophic levels, with bioaccumulation and biomagnification leading to possible toxicity. This study investigates the bioconcentration and toxicity potential of Se(IV) in Nile tilapia (Oreochromis niloticus). After 7 days of exposure, Se concentrations in the fish tissues were in the order: liver ≫ stomach > gills > muscle. In bioconcentration tests, the uptake constant (ka) ranged from 0.34 to 4.68 mL g-1 d-1, while the clearance rate constant (kd) ranged from 0.12 to 0.36 d-1. The tissues presented high bioconcentration factors (BCF) ranging from 2.67 to 12.73, demonstrating the ability of Se(IV) to concentrate in muscle, gills, and stomach. Although the data for the liver could not be fitted by the model used, the measured Se(IV) concentrations were approximately six times higher than those found for the stomach, indicating that the ka, kd, and BCF values were very high. Estimated LC50 values lower than 10 mg L-1 suggested that Se(IV) could be considered very toxic to the fish.